KARAKTERISASI SIFAT FISIK DAN MEKANIK JENDELA KAPAL PRODUK UMKM BERBAHAN BAKU LIMBAH ALUMINIUM - Abitama Mukti Raharjo; Norman Iskandar (JURNAL TEKNIK MESIN, 2015)
The needs of shipping components made from aluminum is increasing. This needs not only for production of new ships but also for old ships spare part. This makes many small and medium industries growing and developing to work in this field. Most of small foundry industry do not use pure aluminum material, but utilizing scrap or reject material from the previous casting material. So this is affect the outcome and quality of the product. UMKM from Tegal City is one of central foundry industry which is the main product is ships component. But the product that produced by this UMKM has been no have any testing on the physical and mechanical properties so that do not have the technical specifications and standards for the manufacturing of ship component. This study aims to examine the mechanical and physical properties of ship window aluminum alloy produced by UMKM toward international ship company quality standards for ship components. Metal casting conducted by using sand casting and examined its physical properties and mechanical properties with a variety of testing methods. The test includes electrical conductivity, hardness, ultimate tensile strength calculations, density, and composition test. The results of the study showed that the material for ship windows produced by UMKM in Tegal is comply the standards, with content for aluminum type is 213.0 or Al-Cu alloy, with the hardness and UTS values 48,8 HRB and 318,67 MPa.